A Novel Approach to Brain Biometric User Recognition. (2016) - Reshmi, K.C.; Muhammed, P. Ihsana; Priya, V.V.; Akhila, V.A.
Abstract: Advances in the field of information technology makes information security is a major part of it. To deal with security, Recognition plays an important role. Now a day the numbers of organizations are using automated person recognition systems to improve customer satisfaction, to enhance operating efficiency and to secure critical resources. The reliable biometric recognition systems to either confirm or determine the individual's identity to servicing their requests. This paper gives a novel approach on user recognition using EEG signals of Brain. EEG is sensitive to the electrical field generated by the electric currents induced in the brain. EEG recordings are acquired with portable and relatively inexpensive devices when compared to the other brain imaging technique like fMRI. The Emotiv EPOC EEG neuro headset has 14 saline electrodes with two reference sensors is used for the acquisition of brainwaves.